How 15‐month‐old infants process morphologically complex forms in an agglutinative language?. (5th February 2020) - Ladányi, Enikő; Kovács, Ágnes M.; Gervain, Judit
Abstract: While phonological development is well‐studied in infants, we know less about morphological development. Previous studies suggest that infants around one year of age can process words analytically (i.e., they can decompose complex forms to a word stem and its affixes) in morphologically simpler languages such as English and French. The current study explored whether 15‐month‐old infants learning Hungarian, a morphologically complex, agglutinative language with vowel harmony, are able to decompose words into a word stem and a suffix. Potential differences between analytical processing of complex forms with back versus front vowels were also studied. The results of Experiment 1 indicate that Hungarian infants process morphologically complex words analytically when they contain a frequent suffix. Analytic processing is present both in the case of complex forms with back and front vowels according to the results of Experiment 2. In light of the results, we argue for the potential relevance of the early development of analytic processing for language development.